The Effect of Syariah People's Business Credit (KUR) And Business Resources on The Productivity of Micro Small and Medium Entrepreneurs (MSME) In Medan, Indonesia - prayoga, Adistia; Rahmayati, Rahmayati (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2023)
This study examines the influence of Sharia People's Business Credit (KUR Syariah) and business resources on the productivity of MSMEs in Medan Marelan District. The research method used is a quantitative research method. The research used in the study entitled the influence of KURS (Shariah People's Business Credit) and Business Resources on MSME Productivity in Medan Marelan District. The type of research used is a descriptive quantitative research type. Where in this study analyzes the influence of independent variables, namely KURS (people's business credit) and business resources on MSME productivity with the dependent variable being MSME productivity. The population of this study is MSME entrepreneurs in Medan Marelan District consisting of 896 MSMEs. The sampling technique used is the Slovin method. From the calculation results above, the sample of this study was rounded up to 90 MSMEs in Medan Marelan District.This result indicates that 82.3% of MSME productivity variations are influenced by these two variables, while 17.7% are influenced by other factors. Therefore, optimizing access to KUR Syariah, business assistance, and innovative strategies are necessary to enhance MSME competitiveness sustainably. These findings confirm that access to sharia financing and the optimization of business resources can significantly improve MSME productivity. Therefore, the government and sharia financial institutions should continue to promote the broader utilization of KUR Syariah and provide assistance in business management. Additionally, MSME actors are encouraged to develop more innovative business strategies, including business digitalization and improved management quality, to enhance competitiveness and sustainable business growth.